PENGARUH DUKUNGAN SOSIAL DAN SCHOOL WELL-BEING TERHADAP MOTIVASI BERPRESTASI SISWA: The Influence of Social Support and School Well-Being on Student Achievement Motivation - Felipus, Indrawati; Amseke, Fredericksen Victoranto (Yayasan Al-Amin Qalbu, 2024)
Achievement motivation is an important need for students to achieve success in learning. The role of teachers, peers and parents is needed as factors of social support and school well-being as students' perceptions of a positive psychological school environment are very important to support an effective learning process in the classroom. The aim of this research is to determine the influence of social support and school well-being on students' achievement motivation at Fatuleu Tengah State High School. The method in this research is quantitative. The data collection tool uses a questionnaire. Participants in this research were 53 class XI students at Fatuleu Tengah State High School. The data analysis technique uses multiple regression analysis. The results of this research show that there is a positive and significant influence of social support and school well-being on the achievement motivation of class students amounted to 97.9% and the remaining 2.1% was explained by other variables